Facultative CAM and photosynthetic electron transport: unravelling the salinity acclimation puzzle in Mesembryanthemum crystallinum - Pilarska, Maria (Frontiers in Plant Science, 2026)
Progressive soil salinisation is a major constraint to agriculture, and deciphering resistance strategies in plants adapted to such harsh environments has the potential for improving salinity tolerance in crops. Efficient regulation of the photosynthetic light reactions is a key element of acclimation to adverse environmental conditions, as it ensures optimal production of reducing power and ATP. The annual halophyte Mesembryanthemum crystallinum has long served as a model plant for studying stress response mechanisms. In this species, exposure to salt stress induces a transition from C3 photosynthesis to crassulacean acid metabolism (CAM). This review summarises the latest findings on the regulation of photosynthetic electron transport (PET) under salinity in M. crystallinum, focusing on their potential dependence on CAM. It also suggests a model in which the plastoquinone pool plays a major role in PET acclimation.